Corporate Social Responsibility and Financial Performance of Automotive Companies: A Basis for Corporate Social Responsibility Framework - Catacutan, Karen Joy; Austria, Kirsten Dayle; Cusipag, Mark Julius; Marcos, Precious; Ramos, Caryl Kate; Tungpalan, Genielhyne (Indonesian Journal of Business Analytics, 2024)
This study determined the relationship between corporate social responsibility (CSR) activities and the financial performance of automotive companies in Tuguegarao City, Cagayan, using data from 2020-2022. Descriptive statistics, financial metrics analysis, ANOVA, and Chi-Square Pearson tests were employed. Results showed that while environmental and ethical CSR initiatives were emphasized, economic community development was less prioritized. No significant differences were found in CSR activities based on firm profiles, and there was no significant link between CSR activities and financial performance. The study recommends a more balanced CSR approach, with greater emphasis on local economic development and partnerships with community and educational institutions. Due to limitations in sample size and data variety, future research should involve a broader participant base.